Predictors of mortality among the neonates transported to referral centre in Delhi, India - Manish Narang; Jaya Shankar Kaushik; Arun Kumar Sharma; M. M. A. Faridi (Wolters Kluwer Medknow Publications, 2013)
A descriptive study was conducted with an objective to determine the predictors of mortality among referred neonates and to ascertain their transport characteristics. A total of 300 consecutive neonates who were transferred to the centre were enrolled in the study. Following information were recorded: maternal details, birth details, interventions before transportation, details of transportation and neonatal condition at arrival. Detailed clinical assessment and management was done as per standard neonatal protocols. Birth weight <1 kg (OR 0.04; 95% CI: 0.006-0.295, P<0.01) and transportation time >1 hour (OR 5.58; 95% CI: 1.41-22.01, P=0.01) were found to be significant predictors for mortality among the transported neonate. Transport characteristics reflect road transport with limited utility of ambulances and lack of trained health personal. Hence to conclude, extreme low birth weight and prolonged transportation time were found to be significant predictors of neonatal mortality among the transported neonate.